Reconnecting Jakarta : A Catalytic Public Space - Raihana Putri Hutami; Purwanita Setijanti (Jurnal Sains dan Seni ITS, 2017)
Urbanization has been a major global issue, especially in the 21st century. This rapid urbanization drives a massive amount of population movements to urban areas and its peripheries, and drastically increased urban density. Although it rises several values and strengthened local economic power, urbanization causes degradation on the spatial discourse. Most urban spaces nowadays are formed by economic-driven factors, and leaving the importance of social relations behind. Urbanization and economic growth in urban areas -- especially in nation’s capital like Jakarta -- resulting a high gap or inequality. The existence of kampong and the modern city reflects the spatial segregation and socio-economic disparities. This leads to social exclusion, where the urban poor are marginalized and alienated from their neighborhood. While the physical separation is inevitably seen, low intensity on social interaction is one of other form of restrictions. The proposed object is a mix function between an outdoor public space and community center, to create a social space that could triggers interaction between social classes and increases social relations. Using urban catalyst studies, this project tries to produce an activity generator. So that the economic-driven urban spaces are not seen as a boundary, but could functions as a social catalyst.